Late Quaternary glacial maxima in southern Patagonia: insights from the Lago Argentino glacier lobe - Romero, Matias (2024)
Determining the timing and extent of Quaternary glaciations around the globe is critical to understanding the drivers behind climate change and glacier fluctuations. Evidence from the southern mid-latitudes indicates that local glacial maxima preceded the global Last Glacial Maximum (LGM), implying that feedbacks in the climate system or ice dynamics played a role beyond the underlying orbital forcings. To shed light on these processes, we investigated the glacial landforms shaped and deposited by the Lago Argentino glacier (50° S), an outlet lobe of the former Patagonian Ice Sheet, in southern Argentina. We mapped geomorphological features on the landscape and dated moraine boulders and outwash sediments using 10Be cosmogenic nuclides and feldspar infrared stimulated luminescence (IRSL) to constrain the chronology of glacial advance and retreat. We report that the Lago Argentino glacier lobe reached more extensive limits prior to the global LGM, advancing during the middle to late Pleistocene between 243–132 ka and during Marine Isotope Stage 3 (MIS 3), culminating at 44.5 ± 8.0 and at 36.6 ± 1.0 ka. Our results indicate that the most extensive advance of the last glacial cycle occurred during MIS 3, and we hypothesize that this was a result of longer and colder winters, as well as increased precipitation delivered by a latitudinal migration of the Southern Westerly Winds belt, highlighting the role of local and regional climate feedbacks in modulating ice mass changes in the southern mid-latitudes.